Beauvoir in time - Altman, Meryl (Brill Rodopi, 2020)
"Beauvoir in Time situates Simone de Beauvoir's The Second Sex in the historical context of its writing and in later contexts of its international reception, from then till now. The book takes up three aspects of Beauvoir's work more recent feminists find embarrassing: "bad sex," "dated" views about lesbians, and intersections with race and class. Through close reading of her writing in many genres, alongside contemporaneous discourses (good and bad novels in French and English, outmoded psychoanalytic and sexological authorities, ethnographic surrealism, the writing of Richard Wright and Franz Fanon), and in light of her travels to the U.S. and China, the author uncovers insights more recent feminist methodologies obscure, showing Beauvoir is still good to think with today"--
Includes bibliographical references and index
Keywords: Beauvoir, Simone de -- 1908-1986 -- Le deuxième sexe; Beauvoir, Simone de / 1908-1986 / Deuxième sexe; Beauvoir, Simone de / 1908-1986 / Criticism and interpretation; Feminism